Treatment of lead-contaminated soil using ground granulated blastfurnace slag - Yiu, Cai Ling (2019)
Lime-activated Ground Granulated Blastfurnace Slag (GGBS) has received lots of attention in stabilization of uncontaminated soils, but limited studies have been conducted to extend the use of lime-activated GGBS to contaminated soils. For this reason, this report investigated the efficiency of lime-GGBS in treating the Pb-contaminated soil. Laboratory tests were conducted to examine the properties of lime-GGBS treated Pb-contaminated soils, including unconfined compressive strength (UCS), leaching, X-ray diffraction (XRD) and scanned electronic microscope (SEM) tests. For 56 days, 0.5% lime content was effective in activating the GGBS as the UCS strength of lime activated GGBS uncontaminated soil was similar to and even higher than that of cement treated soil. For 14 days curing, the addition of Pb decreased the strength of lime GGBS-stabilised soils significantly. The higher Pb concentration, the lower strength, but the strength of lime GGBS-stabilised Pb-contaminated soils increased with curing ages and was close to the strength level of uncontaminated soils for longer curing (i.e.56 days curing). The lime-GGBS was effective in immobilising Pb as the Pb leachability has been significantly decreased from 8000/16000 to less than 500 mg/kg regardless curing ages with the treatment of lime-GGBS. Additionally, the Pb leachability was highly dependent on the pH of soils. The XRD results showed CSH and hydrocerussite were formed in treated soils, which were responsible for lowering Pb leachability in lime GGBS-treated Pb-contaminated soil. The SEM result confirms the formation of CSH.